The Efficiency of Convalescent Plasma Therapy in the Management of Critically Ill Patients Infected With COVID-19: A Matched Cohort Study - Pan, Chun; Chen, Hui; Xie, Jianfeng; Huang, Yingzi; Yang, Yi; Du, Bin; Qiu, Haibo (Frontiers in Medicine, 2022)
Background The convalescent plasma of patients who recover from COVID-19 contains high-titers of neutralizing antibodies, which has potential effects on the viral shedding of SARS-CoV-2 and improving the prognosis of patients with COVID-19. The goal of this study is to clarify the effects of convalescent plasma therapy on the 60-day mortality and negative conversion rate of SARS-CoV-2 during the hospitalization of patients with severe and life-threatening COVID-19 infection. Methods This was a retrospective, case-matched cohort study that involved patients with severe COVID-19 infections. The patients who received convalescent plasma therapy were matched by age, sex, diabetes, hypertension, heart failure, onset of symptoms to hospital admission, respiratory support pattern, lymphocyte count, troponin, SOFA, glucocorticoid, and antiviral agents to no more than three patients with COVID-19 who did not receive convalescent plasma therapy. A Cox regression model and competing risk analysis were used to evaluate the effects of convalescent plasma therapy on these patients. Results Twenty-six patients were in the convalescent plasma therapy group, and 78 patients were in the control group. Demographic characteristics were similar in both groups, except for the SOFA score. Convalescent plasma therapy did not improve 60-day mortality (HR 1.44, 95% CI 0.82-2.51, p=0.20), but the SARS-CoV-2 negative conversion rate for 60 days after admission was higher in the convalescent plasma group (26.9% vs. 65.4%, p=0.002) than in the control. Then, a competing risk analysis was performed, which considered events of interest (the negative conversion rate of SARS– CoV-2) and competing events (death) in the same model. Convalescent plasma therapy improved events of interest (p=0.0002). Conclusions Convalescent plasma therapy could improve the SARS-CoV-2 negative conversion rate but did not improve 60-day mortality in patients with severe and life-threatening COVID-19 infection.